Safety of the APOLLO Onyx delivery microcatheter for embolization of brain arteriovenous malformations: results from a prospective post-market study. (1st February 2021) - Meyers, Philip M; Fifi, Johanna T.; Cockroft, Kevin M.; Miller, Timothy R.; Given, Curtis A.; Zomorodi, Ali R.; Jagadeesan, Bharathi D.; Mokin, Maxim; Kan, Peter; Yao, Tom L.; Diaz, Orlando; Huddle, Daniel; et al.
Abstract : Background: Catheter retention and difficulty in retrieval have been observed during embolization of brain arteriovenous malformations (bAVMs) with the Onyx liquid embolic system (Onyx). The Apollo Onyx delivery microcatheter (Apollo) is a single lumen catheter designed for controlled delivery of Onyx into the neurovasculature, with a detachable distal tip to aid catheter retrieval. This study evaluates the safety of the Apollo for delivery of Onyx during embolization of bAVMs. Methods: This was a prospective, non-randomized, single-arm, multicenter, post-market study of patients with a bAVM who underwent Onyx embolization with the Apollo between May 2015 and February 2018. The primary endpoint was any catheter-related adverse event (AE) at 30 days, such as unintentional tip detachment or malfunction with clinical sequelae, or retained catheter. Procedure-related AEs (untoward medical occurrence, disease, injury, or clinical signs) and serious AEs (life threatening illness or injury, permanent physiological impairment, hospitalization, or requiring intervention) were also recorded. Results: A total of 112 patients were enrolled (mean age 44.1±17.6 years, 56.3% men), and 201 Apollo devices were used in 142 embolization procedures. The mean Spetzler–Martin grade was 2.38. The primary endpoint was not observed (0/112, 0%). The catheter tip detached during 83 (58.5%) procedures, of which 2 (2.4%) were unintentional and did not result in clinical sequelae. At 30 days, procedure related AEs occurred in 26 (23.2%) patients, and procedure-related serious AEs in 12 (10.7%). At 12 months, there were 3 (2.7%) mortalities, including 2 (1.8%) neurological deaths, none of which were device-related. Conclusion: This study demonstrates the safety of Apollo for Onyx embolization of bAVMs. Clinical trial registration: CNCT02378883 .